2015
DOI: 10.1186/s13568-015-0127-2
|View full text |Cite
|
Sign up to set email alerts
|

Description of the interaction between Candida albicans and macrophages by mixed and quantitative proteome analysis without isolation

Abstract: Candida albicans is an opportunistic pathogen that causes fatal diseases in immunocompromised hosts. Host resistance against C. albicans relies on ingestion of the pathogen by macrophages. Analysis of the escaping behavior of C. albicans from macrophages is required to understand the onset of systemic candidiasis. In this study, native interactions of C. albicans with macrophages were investigated by proteome analysis using high efficiency of long monolithic silica capillary column. Using this system, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…Kitahara et al analyzed the escaping behavior of C. albicans from macrophages by using mixed and quantitative proteome analysis in isolation [124]. The authors identified five proteins from macrophages and 237 proteins from C. albicans as candidate interaction-specific molecules.…”
Section: Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kitahara et al analyzed the escaping behavior of C. albicans from macrophages by using mixed and quantitative proteome analysis in isolation [124]. The authors identified five proteins from macrophages and 237 proteins from C. albicans as candidate interaction-specific molecules.…”
Section: Proteomicsmentioning
confidence: 99%
“…Meanwhile, C. albicans -induced macrophage proteins were linked with a chaperone and apoptosis. The authors postulated that C. albicans can endure the harsh environment inside macrophages through upregulation of stress-related proteins, while the escape of C. albicans from macrophages could be associated with the production of glucose from a β-oxidation pathway and downregulation of chaperone HSPA1A- and apoptosis-associated protein, NOA1-syntheses, in macrophages [124]. In summary, proteome research on host–pathogen interaction with respect to Candida infection is still an emerging field.…”
Section: Proteomicsmentioning
confidence: 99%
“…This approach has also been applied for the first report of a mixed and quantitative dual proteome analysis that has been recently published based on the interaction of C. albicans with murine macrophages. The authors identified 483 C. albicans and 1253 macrophage proteins in total, where of 227 C. albicans and five macrophage proteins of the co-culture experiment exhibited a differential expression compared to separate C. albicans and macrophage mono-culture controls [161]. Reporter ion quantification using the TMT labeling approach was applied to reveal relative quantitative changes on the proteome level [161].…”
Section: Challenges In the Simultaneous Dual Proteome Analysis Of mentioning
confidence: 99%
“…The authors identified 483 C. albicans and 1253 macrophage proteins in total, where of 227 C. albicans and five macrophage proteins of the co-culture experiment exhibited a differential expression compared to separate C. albicans and macrophage mono-culture controls [161]. Reporter ion quantification using the TMT labeling approach was applied to reveal relative quantitative changes on the proteome level [161]. The protein median normalization approach cannot be recommended for all types of experimental setups and outcomes, in particular when a certain response on the actual protein level shows a significant but moderate differential regulation (e.g., 2.5-fold up) of numerous proteins in one direction and a drastic differential regulation (e.g., 25-fold down) of few proteins in the other direction.…”
Section: Challenges In the Simultaneous Dual Proteome Analysis Of mentioning
confidence: 99%
“…Once activated, they act directly by destroying bacteria, parasites, viruses, fungi and tumor cells with reactive oxidants and hydrolytic enzymes, or indirectly by releasing specific mediators such as interleukin-1, tumor necrosis factor-alpha and others which can regulate other cells' activities. They are also responsible for processing the antigens and presenting the digested peptides to lymphocytes, while playing the leading role in damage repair (9)(10)(11) Original article and other compromises in host defense due to use of these therapies, it is important to reverse or at least lessen immunosuppresion in this patients (2,4). Fungal infections are treated with antifungal drugs.…”
Section: Introductionmentioning
confidence: 99%